Academic language mastery - LeMoine, Noma; Soto, Ivannia (Academic Language Mastery Series, 2017)
By now it's a given: if we're to help our ELLs and SELs access the rigorous demands of today's content standards, we must cultivate the "code" that drives school success: academic language. Look no further for assistance than this much-anticipated series from Ivannia Soto, in which she invites field authorities Jeff Zwiers, David and Yvonne Freeman, Margarita Calderon, and Noma LeMoine to share every teacher's need-to-know strategies on the four essential components of academic language. The subject of this volume is culture. Here, Noma LeMoine makes clear once and for all how culturally and linguistically responsive pedagogy validates, facilitates, liberates, and empowers ethnically diverse students. With this volume as your roadmap, you'll learn how to: " Implement instructional strategies designed to meet the linguistic and cultural needs of ELLs and SELs " Use language variation as an asset in the classroom " Recognize and honor prior knowledge, home languages, and cultures The culture and language every student brings to the classroom have vast implications for how to best structure the learning environment. This guidebook will help you get started as early as tomorrow. Better yet, read all four volumes in the series as an all-in-one instructional plan for closing the achievement gap